ANALISIS ARUS BOCOR ISOLATOR PADA JTM DI PLN ULP MOJOSARI DALAM KONDISI KERING DAN BASAH - Ramadhan, Muhammad Dicky; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
This research discusses about the leakage current analysis of polluted ceramic disk insulators at PLN ULP Mojosari. So that conditions in the laboratory are the same as in the field, leakage current testing is carried out in dry and wet conditions, with variations in wet conditions using rainfall of 25.49 mm, 45.79 mm, and 96.37 mm to simulate rainfall in Indonesia, according to data from BMKG. In this research, a polluted plate insulator consisting of 2 disk insulators is used according to conditions in the field. The test voltage variations used range from 11 kV to 24 kV. From the test results it was found that pollutants on the insulator and rainfall had an effect on the leakage current value, because from the results of testing the pollutant content it was found that the pollutants present were metal and semiconductor which could reduce the insulating ability of the insulator if theseelements stuck to the surface of the insulator . In XRF testing, pollutant elements that are difficult to dissolve in water were found, namely Ti (Titanium) at 1.29%, V (Vanadium) at 0.04%, Cr (Chrome) at 5.97%, Mn (Manganese) at 7.14 %, Fe (Iron) at 11.2%, and Ni (Nickel) at 7.10%. Meanwhile, in the XRF-H method, the element Ti (Titanium) was 1.8%, V (Vanadium) was 0.30%, Cr (Chrome) was 14.4% and Mn (Manganese) was 36.1%. In testing pollutant insulators with a voltage of 20 kV in dry conditions, the leakage current value was 136.43 µA. Then, in testing wet conditions with artificial rainfall of 25.49 mm, 45.79 mm, and 96.37 mm, leakagecurrent values were obtained at 142 µA, 214.83 µA, and 290.63 µA, respectively. In this research, it was found that the greater the artificial rainfall and the test voltage provided, the greater the value of the leakage current flowing through the pollutant insulator. Leakage current flowing on the surface of polluted insulators will also cause electrical power losses and electrical energy losses. The energy loss values obtained at a test voltage of 20 kV are 23.90 kWh for dry conditions, 24,88 kWh for 25,49 mm rainfall, 37,64 kWh for 45,79 mm rainfall, and 50.92 kWh for dr 96.37 mm rainfall. Keyword: Leakage Current, Disk Insulator, Pollutant, Wet, Dry